Mechanisms and pathways linking kindergarten behavior problems with mid-life employment earnings for males from low-income neighborhoods - Vergunst Francis; Vitaro Frank; Brendgen Mara; Larose Marie-Pier; Girard Alain; Tremblay Richard E.; Côté Sylvana M. (WILEY, 2025)
Childhood behavior problems are associated with reduced labor market participation and lower earnings in adulthood, but little is known about the pathways and mechanisms that explain these associations. Drawing on a 33-year prospective birth cohort of White males from low-income backgrounds (n = 1040), we conducted a path analysis linking participants' teacher-rated behavior problems at age 6 years-that is, inattention, hyperactivity, aggression-opposition, and low prosociality-to employment earnings at age 35-39 years obtained from tax records. We examined three psychosocial mediators at age 11-12 years (academic, behavioral, social) and two mediators at age 25 years (non-high school graduation, criminal convictions). Our findings support the notion that multiple psychosocial pathways-especially low education attainment-link kindergarten behavior problems to lower employment earnings decades later.